Management of patients with chronic rhinosinusitis during the COVID‐19 pandemic—An EAACI position paper. Issue 3 (6th March 2021) - Klimek, Ludger; Jutel, Marek; Bousquet, Jean; Agache, Ioana; Akdis, Cezmi A.; Hox, Valerie; Gevaert, Philippe; Tomazic, Peter Valentin; Rondon, Carmen; Cingi, Cemal; Toppila‐Salmi, Sanna; Karavelia, Aspasia; et al.
Abstract: Background: Chronic rhinosinusitis is regarded as a chronic airway disease. According to WHO recommendations, it may be a risk factor for COVID‐19 patients. In most CRSwNP cases, the inflammatory changes affecting the nasal and paranasal mucous membranes are type‐2 (T2) inflammation endotypes. Methods: The current knowledge on COVID‐19 and on treatment options for CRS was analyzed by a literature search in Medline, Pubmed, international guidelines, the Cochrane Library and the Internet. Results: Based on international literature, on current recommendations by WHO and other international organizations as well as on previous experience, a panel of experts from EAACI and ARIA provided recommendations for the treatment of CRS during the COVID‐19 pandemic. Conclusion: Intranasal corticosteroids remain the standard treatment for CRS in patients with SARS‐CoV‐2 infection. Surgical treatments should be reduced to a minimum and surgery preserved for patients with local complications and for those with no other treatment options. Systemic corticosteroids should be avoided. Treatment with biologics can be continued with careful monitoring in noninfected patients and should be temporarily interrupted during the course of the COVID‐19 infection.